Consumer Involvement Towards Ready-to-Eat Breakfast Cereals in India : An Application of Revised Product Involvement Inventory (RPII) - Simon, Simi; Murali Manohar, B. (Indian Journal of Marketing, 2017)
Consumer behaviour studies are gaining relevance in the current Indian retail scenario against the backdrop of various challenges that are posed by changed consumer lifestyles. Consumer involvement in the purchase decision process concept has been an interesting topic to consumer researchers as well as other practitioners. It affects the purchase decision of consumers which includes information search and the actual buying process that are directly related to consumer buying behaviour. The goal of the study was to explore and discuss the applicability of the revised product involvement inventory (RPII) to rate the level of involvement in the buying behaviour of Indian consumers of RTE breakfast cereals. The study was carried out from January 2015 to 2016. A research model was developed in order to understand the relationship between the constructs of involvement with reference to its sub - scales of interest and importance. A survey method was used for data collection. The data was analyzed and interpreted using structural equation modelling (SEM). The results revealed that RPII represents a reliable measurement scale for measuring involvement in the Indian market. In the study, it is proved that consumer involvement with subscale of interest has more significance among RTE breakfast cereal consumers in India. The dimensions of involvement such as brand loyalty, product information search, time taken to choose the product, and in addition, the psychological tension element were found to significantly affect consumer decision making.